THREE NEW SPECIES OF DINOCHLOA (POACEAE, BAMBUSOIDEAE) WITH ERECT CULM SHEATH BLADES FROM SULAWESI, INDONESIA - Elizabeth Anita Widjaja (Research Center for Biology, 2009)
WIDJAJA, E.A. 2009. Three new species of Dinochloa (Poaceae, Bambusoideae) with erect culm sheath blades from Sulawesi, Indonesia. Reinwardtia 12(5): 435–440. –– Dinochloa aopaensis, D. morowaliensis, and D. petasiensis, are described as new. They are characterized by their erect culm sheath blades, but are distincted by a combination of characters of the auricle and ligule of the culm sheath, auricle and ligule of the leaf sheath and the pubescence of the leaf sheath. A key to the species of Malesian Dinochloa with erect culm sheath blades is presented.